Effect of concomitant use of antihypertensives and immune check point inhibitors on cancer outcomes. Issue 7 (July 2021) - Kichenadasse, Ganessan; Miners, John O.; Mangoni, Arduino A.; Rowland, Andrew; Sorich, Michael J.; Hopkins, Ashley M.
Abstract : Objectives: Antihypertensives and cancer have a complex relationship. Among the antihypertensives, renin–angiotensin system inhibitors have strong immune modulatory activities that may affect immune check point inhibitors-related outcomes in cancer patients. We evaluated the association between concomitant use of renin–angiotensin system inhibitors and other antihypertensive agents with survival/toxicity outcomes from atezolizumab. Methods: A post hoc analysis of individual patient data from seven clinical trials of lung, renal or urothelial cancers was performed. Users and nonusers of antihypertensive classes were compared for overall survival, progression-free survival and immune adverse events. Cox proportional hazards were calculated between the groups and reported as hazards ratio and 95% confidence interval (95% CI). Results: Of the 3695 patients, 2539 were treated with atezolizumab and the rest with chemotherapy. Twenty-four percent of patients were on a renin–angiotensin system inhibitor at trial commencement. No statistically significant difference in overall survival (hazard ratio 0.92, 95% CI 0.79–1.07, P = 0.29), progression-free survival (hazard ratio 0.95, 95% CI 0.84–1.08, P = 0.42) or immune adverse events (odds ratio 0.94, 95% CI 0.76–1.15, P = 0.55) between renin–angiotensin system inhibitor users and nonusers were identified in the atezolizumab-treated cohort. Other classes of antihypertensives were also not associated with survival. Conclusion: Concomitant use of antihypertensives including RASi was not associated with survival and immune-related safety outcomes during atezolizumab therapy for solid cancers. Future studies should evaluate the association between antihypertensives and other ICI as well as ICI combination interventions in clinical trials and real-world settings.